2019
DOI: 10.1080/20013078.2019.1669881
|View full text |Cite
|
Sign up to set email alerts
|

Circulating extracellular vesicle content reveals de novo DNA methyltransferase expression as a molecular method to predict septic shock

Abstract: Extracellular vesicles (EVs) are mRNA‐containing cell fragments shed into circulation during pathophysiological events. DNA methyltransferases (DNMT1, DNMT3A, and DNMT3B) regulate gene expression by modifying DNA methylation and altering transcription. Sepsis is a systemic insult resulting in vascular dysfunction, which can lead to shock and death. We analysed plasma from ICU patients for circulating EV numbers, defined as particles isolated from 1 mL plasma at 21,000xg, and DNMTs mRNA content as prognostic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 70 publications
(84 reference statements)
0
44
0
Order By: Relevance
“…There is an extensive system of proteins in the cells involved in writing the methylation pattern on DNA via de-novo methylation (DNMT3A and DNMT3B) and copying methylation patterns during DNA replication via methylation maintenance (DNMT1) (17). Reportedly, circulating extracellular vesicle DNMTs are highly correlated with sepsis severity and may serve as a predicting factor (34). As observed during the current study, DNMT1 was upregulated in CLP mice, which substantiated the findings of a previous study on LPS endotoxic shock models (35).…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive system of proteins in the cells involved in writing the methylation pattern on DNA via de-novo methylation (DNMT3A and DNMT3B) and copying methylation patterns during DNA replication via methylation maintenance (DNMT1) (17). Reportedly, circulating extracellular vesicle DNMTs are highly correlated with sepsis severity and may serve as a predicting factor (34). As observed during the current study, DNMT1 was upregulated in CLP mice, which substantiated the findings of a previous study on LPS endotoxic shock models (35).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DNA methylation acts as a switch for transcriptional activation or repression of genes that are essential for development and proper cellular functioning. Till date, DNMT1, DNMT3A, DNMT3B, DNMT2 and DNMT3L are known mammalian DNMTs [ [421] , [422] , [423] , [424] ]. Whereas activation induced cytidine deaminase (AICDA) and thymine DNA glycosylase (TDG) are examples of enzymes that demethylate DNA and protect unmethylated regions of mammalian genomes from de novo methylation [ 425 , 426 ].…”
Section: Sevs In Cancer Liquid Biopsymentioning
confidence: 99%
“…showed that circulating EVs had significantly higher loads of DNA methyltransferase (DNMT) mRNA, which regulates gene expression. [ 96 ] Specifically, more severely ill patients showed increases in the ratio of de novo methylating factors DNMT3A and DNMT3B to the maintenance methylating factor DNMT1 encapsulated within these circulating EVs. [ 96 ] Research has also shown sepsis‐induced differential expression of other EV‐associated molecules, including miRNAs.…”
Section: Endogenous Roles Of Evs In Sepsismentioning
confidence: 99%